Development and Validation of a 3D Hologram-Based Learning Media for Emergency Preparedness in Islamic Boarding Schools - Tiara Kamila Dyanti; Andi Subandi; Rts Netisa Martawinarti; Yosi Oktarina (STIKep PPNI Jawa Barat, 2025)
Background: Islamic boarding schools (pesantren) have distinctive educational settings, yet emergency preparedness education remains limited by conventional learning methods. Objective: This study aimed to develop and validate a three-dimensional (3D) hologram-based learning media on school safety zones and first aid for students in Islamic boarding schools. Methods: This research employed a Research and Development (R&D) approach using the 4D model, consisting of the Define, Design, and Develop stages. Validation was conducted by two material experts and two media experts using standardized assessment instruments covering aspects of content accuracy, visual quality, and practicality. Data were analyzed descriptively to determine the feasibility level of the developed media. Results: Validation by material experts yielded an average score of 93.33%, while media experts obtained 92.94%, both categorized as very feasible. These findings indicate that the 3D hologram-based learning media meets both substance and technical standards required for preparedness and first-aid education. Conclusion: The developed 3D hologram-based learning media was declared very feasible based on expert validation, making it a valid and appropriate educational tool for future implementation in nursing and health education programs.